Pancreatic Disorders and Diabetes Mellitus-A Review - Rahman, Md Hafizur; Ali, Md Yusuf (Faridpur Medical College Journal, 2016)
Diabetes mellitus is a common disease among patients with pancreatic cancer and chronic pancreatitis. Hyperinsulinemia and peripheral insulin resistance are the prevailing diabetic traits in pancreatic cancer, whereas reduced islet cell mass and impaired insulin secretion are typically observed in chronic pancreatitis. Whether or not a causal relationship exists between diabetes and pancreatic carcinoma is an intriguing but unanswered question. Diabetes often precedes pancreatic cancer and is thus regarded as a potential risk factor for malignancy. Conversely, pancreatic cancer may secrete diabetogenic factors. Given these findings, there is increasing interest in whether close monitoring of the glycaemic profile may aid early detection of pancreatic tumor lesions. Exocrine pancreatic insufficiency is frequently associated with diabetes, with high prevalence in both insulin-dependent and insulinindependent patients. The incidence of diabetes caused by exocrine pancreatic disease appears to be underestimated and may comprise 8% or more of the general diabetic patient population. Non-endocrine pancreatic disease can cause diabetes by multiple mechanisms. Genetic defects have been characterized, resulting in a syndrome of both exocrine and endocrine failure. Regulation of beta cell mass and physiological incretin secretion are directly dependent on normal exocrine function. Algorithms for diagnosis and therapy of diabetes should therefore address both endocrine and exocrine pancreatic function. Faridpur Med. Coll. J. Jan 2015;10(1): 36-39